Comparative review on vertical deformation in deep excavations: Insights from BU and TD methods - Wen, Zhou; Amizatulhani, Abdullah; Doh, Shu Ing; Jing, Chen (Elsevier Ltd., 2025)
With the rapid pace of urbanization, controlling vertical deformation in deep excavations has become increasingly important. This study reviews over one hundred recent publications and systematically compares the Bottom-up (BU) and Top-down (TD) methods using four key indicators: surface settlement, vertical displacement of retaining walls, column settlement, and basal heave. BU features a simple construction sequence and stable column behavior but is prone to greater settlement and heave when support stiffness or dewatering is insufficient. TD, by casting floor slabs in advance, reduces surface settlement by approximately 21 %–26 % and basal heave by 14.1 %–38.6 %, yet increases column settlement by 16.7 %, showing a two-stage “initial uplift–subsequent settlement” response. When surface settlement is normalized as the settlement-to-depth ratio, BU curves can be unified into a single design envelope, while vertical displacement of retaining walls, column settlement, and basal heave exhibit distinct evolution patterns. This review establishes a unified settlement envelope and a concise multi-indicator comparative dataset, providing practical reference for excavation scheme selection and optimization.